PENDEKATAN SOMATIC, AUDITORY, VISUALLY, INTELECTUALLY (SAVI) TERHADAP KEMAMPUAN MEMBACA PERMULAAN PADA ANAK AUTIS DI SDLB - Qoyyimah, Adinul (Jurnal Pendidikan Khusus, 2016)
ABSTRACT The research about the influence of Somatic, Auditory, Visually, Intellectually (SAVI) approach toward beginning reading ability to autism children in SDLBN Bendo Blitar was set background by the autism children’s ability in beginning reading (reading alphabets, syllables, words, and simple sentences) which still needed to be developed, because they were quickly bored with the monotone material and less interesting media used so the researcher gave fun and active learning using Somatic, Auditory, Visually, Intellectually (SAVI) approach. The learning activity of beginning reading with Somatic, Auditory, Visually, Intellectually (SAVI) approach was not applied yet in SDLBN Bendo Blitar. The purpose of this research was to prove whether there was influence of Somatic, Auditory, Visually, Intellectually (SAVI) approach toward beginning reading ability to autism children in SDLBN Bendo Blitar. The method used in this research involved quantitative approach with pre experiment kind using one group pre test – post test design. The sampling technique in this research used purposive sample. The techniques of data collection were observation, test, and documentation. There were two things which should be done to assess the beginning reading ability of autism children i.e. the test, before the autism children were given treatment with Somatic, Auditory, Visually, Intellectually (SAVI) approach and the test, after they were given treatment with Somatic, Auditory, Visually, Intellectually (SAVI) approach. The data analysis technique of research result used statistic non parametric with Wilcoxon Match Pairs Test. The research result indicated that the average value of beginning reading test which was obtained before using Somatic, Auditory, Visually, Intellectually (SAVI) approach was 40,1 while the average value of beginning reading test which was obtained after using Somatic, Auditory, Visually, Intellectually (SAVI) approach was 76,56. It indicated that there was significant enhancement. In addition, the research result also indicated that Z counted = 2,2 was greater than Z table = 1,96 with critic value 5%. If Z counted = 2,2 > Z table = 1,96 which meant that Ho was refused and Ha was accepted so it could be concluded that there was influence of Somatic, Auditory, Visually, Intellectually (SAVI) approach toward beginning reading ability to autism children in SDLBN Bendo Blitar.     Keywords:  beginning reading, SAVI approach